2015
DOI: 10.1002/brb3.317
|View full text |Cite
|
Sign up to set email alerts
|

Temporospatial identification of language‐related cortical function by a combination of transcranial magnetic stimulation and magnetoencephalography

Abstract: IntroductionIdentification of language-related cortical functions can be carried out noninvasively by transcranial magnetic stimulation (TMS) and magnetoencephalography (MEG), which allow for lesion-based interrogation and global temporospatial investigation of cortices, respectively. Combining these two modalities can improve the accuracy of the identification, but the relationships between them remain unclear. We compared TMS and MEG responses during the same language task to elucidate their temporospatial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, in case of higher-order language functions the motor system might not necessarily be activated. In this case, speech reaction time may serve as a behavioral measure for testing TMS-induced modulation of brain functions (Shinshi et al, 2015). Various studies investigated therapeutic aspects of inhibitory or facilitatory brain stimulation during stroke rehabilitation.…”
Section: Virtual Lesion Studies Transcranial Stimulation Methodsmentioning
confidence: 99%
“…However, in case of higher-order language functions the motor system might not necessarily be activated. In this case, speech reaction time may serve as a behavioral measure for testing TMS-induced modulation of brain functions (Shinshi et al, 2015). Various studies investigated therapeutic aspects of inhibitory or facilitatory brain stimulation during stroke rehabilitation.…”
Section: Virtual Lesion Studies Transcranial Stimulation Methodsmentioning
confidence: 99%
“…In another recent study, Shinshi and colleagues [118] used TMS and MEG to investigate the role of the left pIFG in picture naming. In a first experiment, the authors showed that high-frequency 40 Hz triple pulse TMS over the left pIFG but not right pIFG significantly delayed naming latencies when applied 300 or 375 ms after picture presentation.…”
Section: Mapping Adaptive Plasticity In the Healthy Language Networkmentioning
confidence: 99%
“…Subsequent TMS studies have further established a direct relation between the left anterior temporal lobe (ATL; Pobric, Jefferies, & Lambon Ralph, 2007, left middle temporal gyrus (MTG; Acheson, Hamidi, Binder, & Postle, 2011;Schuhmann, Schiller, Goebel, & Sack, 2012), and left IFG (Schuhmann, Schiller, Goebel, & Sack, 2009;Shinshi et al, 2015;Wheat et al, 2013) in picture naming. Of note, event-related single-and triple-pulse TMS studies have provided a more finegrained picture with respect to the temporal dynamics of picture naming, locating the involvement of the IFG at around 300 ms after picture onset, whereas MTG and STG may function as a feed-forward monitoring system around this time point.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical activity during this task has been located in a large left frontotemporal network stretching from the interior frontal to posterior superior temporal and inferior parietal regions (Indefrey, 2011;Indefrey & Levelt, 2004). Using TMS, which applies an ultra-short electromagnetic pulse that creates an electric current in superficial cortical nerve tissue, an engagement of the posterior superior temporal gyrus (pSTG), middle temporal gyrus (MTG), anterior temporal lobe (ATL), and inferior frontal gyrus (IFG) has been demonstrated (Acheson, Hamidi, Binder, & Postle, 2011;Mottaghy et al, 1999;Pobric, Jefferies, & Lambon Ralph, 2007, 2010, Schuhmann, Schiller, Goebel, & Sack, 2009Shinshi et al, 2015;Sparing et al, 2001;Töpper, Mottaghy, Brügmann, Noth, & Huber, 1998;Wheat et al, 2013). Furthermore, cortical excitability can be modulated by applying a constant weak electric current between two electrodes affixed on the scalp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation